2019
DOI: 10.2196/12264
|View full text |Cite
|
Sign up to set email alerts
|

Using Twitter to Detect Psychological Characteristics of Self-Identified Persons With Autism Spectrum Disorder: A Feasibility Study

Abstract: Background More than 3.5 million Americans live with autism spectrum disorder (ASD). Major challenges persist in diagnosing ASD as no medical test exists to diagnose this disorder. Digital phenotyping holds promise to guide in the clinical diagnoses and screening of ASD. Objective This study aims to explore the feasibility of using the Web-based social media platform Twitter to detect psychological and behavioral characteristics of self-identified persons with ASD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 37 publications
2
34
1
Order By: Relevance
“…A higher number in “analytic” reflects formal, logical, and hierarchical thinking. These results are not consistent with Hswen et al (2019) who found the emotional patterns consistent with the diagnosis of ASD in tweets of self-identified individuals. This difference could be attributed to the samples in each study.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…A higher number in “analytic” reflects formal, logical, and hierarchical thinking. These results are not consistent with Hswen et al (2019) who found the emotional patterns consistent with the diagnosis of ASD in tweets of self-identified individuals. This difference could be attributed to the samples in each study.…”
Section: Discussioncontrasting
confidence: 96%
“…Beykikhoshk et al (2015) compared ASD-related tweets with non-ASD-related tweets and identified differences in the types of words used. Of interest, the words “son” and “boy” occurred with higher frequency than “female” and “girl.” Hswen et al (2019) examined the feasibility of using Twitter as a platform to enhance the diagnosis of ASD. The authors extracted Twitter data from individuals who self-identified with ASD and analyzed text content and timing of tweets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work incorporating Twitter data has proven useful in early recognition and characterization in a public emergency ( Cassa et al, 2013 ) and sleep profiles possibly linked with psychosocial issues ( McIver et al, 2015 ), influenza predictions ( Nagar et al, 2014 ) and identification of food poisoning ( Harris et al, 2017 ). Additionally, Twitter data analysis has been consistent with clinical characteristics of autism spectrum disorder ( Hswen et al, 2019 ) and schizophrenia ( Hswen, Naslund, Brownstein, & Hawkins, 2018a , 2018b ). Literature suggests the potential to leverage Twitter data in order to support public health initiatives such as early illness detection ( Hswen et al, 2018a , 2018b ) and suicide prevention ( Hswen et al, 2019 ).…”
Section: Introductionsupporting
confidence: 56%
“…Tweets are limited to 280 characters and have been recognized as a source of organic sentiment and opinions [ 25 ]. The Twitter platform has been widely recognized as a source to monitor public sentiment across a spectrum of health-related issues, including mental health [ 26 - 28 ], vaccination [ 29 ], and smoking [ 30 ]. Most recently, Twitter has emerged as a potential source of information for capturing hospital and health care experiences of sexual minorities [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%